Hydraulic operating temperature control of a loop heat pipe. (July 2015) - Joung, Wukchul; Gam, Kee Sool; Kim, Yong-Gyoo; Yang, Inseok
Abstract: In this work, a hydraulic operating temperature control of loop heat pipes (LHPs) was proposed to achieve a precise, stable, and theoretically predictable operating temperature control. To this end, a pressure controlled LHP was devised to control the saturated vapor temperature at the evaporator by applying hydraulic action on the compensation chamber with an immiscible control gas. In particular, by forming an isothermal region in the vapor transport line, it was attempted to control the temperature of the isothermal region, and the resulting operating temperature controllability was investigated in terms of stability, precision, and predictability. Theoretical basis and limitations of the proposed method were established based on the thermo-hydraulic operating principles of the LHPs, and experimental validation was performed using Dowtherm A as a working fluid and helium as the control gas. Test results showed that the devised pressure controlled LHP was able to control the isothermal region temperature within the stability of 25 mK, and the resolution of the temperature control was around 60 mK at 100 Pa change in the control gas pressure. Large scale operating temperature change was also possible, and a guide to achieve an effective operating temperature control was suggested. Details of the design and fabrication of the devised pressure controlled LHP was also provided.